Green-Synthesized Ag and ZnO Nanoparticles using Cassia fistula Leaf Extract: Biocompatibility and Growth Response in Early Plant Development - Rabbani, A H M Maniruzzaman; Jannat, Syeda Nyema; Shishir, Md. Shahed Al; Alam, Md. Shaheen; Rahman, Atiqur; Alam, Md. Shohidul (Fundamental and Applied Agriculture, 2025)
Green synthesis of metal nanoparticles offers an eco-friendly alternative to conventional chemical methods, with promising applications in agriculture. However, the phytotoxicity of such nanoparticles (NPs), particularly silver (Ag-NPs) and zinc oxide (ZnO-NPs), remains poorly understood. This study investigates the green synthesis, characterization, and biological effects of Ag-NPs and ZnO-NPs using aqueous leaf extracts of Cassia fistula, a plant rich in phytochemicals. UV-Vis spectroscopy confirmed successful synthesis, revealing characteristic peaks at 479 nm (Ag-NPs) and 241 nm (ZnO-NPs). Energy band gaps were calculated as 2.34 eV for Ag-NPs and 4.13 eV for ZnO-NPs. To assess biocompatibility and phytotoxicity, the nanoparticles were tested on seed germination, root and shoot growth, and biomass accumulation in five crop species: Oryza sativa (rice), Brassica napus (canola), Raphanus sativus (radish), Solanum lycopersicum (tomato), and Ipomoea aquatica (water spinach). Both NPs showed concentration-dependent effects: low to moderate doses enhanced germination and seedling vigor, whereas higher doses delayed germination and reduced growth. Ag-NPs were generally more phytotoxic, particularly inhibiting root elongation. ZnO-NPs exhibited a biphasic response - stimulatory at lower concentrations, inhibitory at higher levels. Seedling biomass decreased with increasing NP concentration, with Ag-NPs causing more severe reductions.These findings highlight that while green-synthesized nanoparticles hold agricultural potential, their use must be carefully optimized to avoid phytotoxic effects. The Cassia fistula-mediated synthesis presents a sustainable, biocompatible route for generating functional nanoparticles capable of influencing early plant development.